2021
DOI: 10.15695/jstem/v4i2.09
|View full text |Cite
|
Sign up to set email alerts
|

High School Students’ Learning During the COVID Pandemic: Perspectives from Health Sciences and Technology Academy Participants

Abstract: This paper examines the perspectives of Health Sciences and Technology Academy (HSTA) participants as they navigate through their West Virginia (WV) high school learning environments (i.e., in-person, blended/hybrid, complete virtual) during the novel coronavirus, SARS-CoV-19 (COVID-19) pandemic. In March of 2020, the participants in this out-of-school-time (OST) academic enrichment program for exceptionally driven, yet underprivileged, at-risk students, with over 70% living in rural areas, started receiving r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…Lastly, teachers reported that they care about students academically in distance classes, and care more about students emotionally in face-to-face classes, i.e., distance learning focuses on academic issues and not emotional bonds. Lastly, comparing in-person learning, virtual learning, and blended/hybrid learning in an educational program for disadvantaged (exceptionally driven) students, McKendall et al (2021) found significant differences perceived availability of help, feedback, and support from teachers. However, the small effect sizes led the authors to conclude that there is only negligible practical significance.…”
Section: Comparison Between Environmentsmentioning
confidence: 97%
“…Lastly, teachers reported that they care about students academically in distance classes, and care more about students emotionally in face-to-face classes, i.e., distance learning focuses on academic issues and not emotional bonds. Lastly, comparing in-person learning, virtual learning, and blended/hybrid learning in an educational program for disadvantaged (exceptionally driven) students, McKendall et al (2021) found significant differences perceived availability of help, feedback, and support from teachers. However, the small effect sizes led the authors to conclude that there is only negligible practical significance.…”
Section: Comparison Between Environmentsmentioning
confidence: 97%
“…Se emplearon métodos estadísticos descriptivos de evaluación de consistencia interna de los instrumentos aplicados, mediante el software estadístico SPSS (para ambos instrumentos se obtuvieron coeficientes Alpha de Cronbach superiores a 0,78). Con el objetivo de identificar el efecto de la implementación de los principios DUA, se realizaron mediciones pre y postest de la percepción de los estudiantes respecto a sus habilidades C y S-E., y ambos resultados se analizaron mediante los coeficientes Phi y V de Cramer para mostrar la fuerza de la correlación entre las variables categóricas (habilidades medidasaplicación de la estrategia), de 0-ninguna a 1.0-perfecta (McKendall et al, 2021).…”
Section: Materiales Y Métodosunclassified
“…The transition to online environments had different impacts on students. Those more in-needed of school, more at-risk, with less means of access (McKendall et al, 2021) as well as those more dependent on teachers, more passive learners, less autonomous, without self-study and self-regulation skills (Tomasik, Helbling, & Moser, 2020;Yang, 2020) suffered more seriously. Then, students' profile and characteristics like ability to change and adapt became a key resource for students to be succeed and go through all the difficulties they faced throughout those learning environments (Martin, Collie, & Nagy, 2021).…”
Section: Covid-19 Pandemic Impact On School Studentsmentioning
confidence: 99%
“…Then, students' profile and characteristics like ability to change and adapt became a key resource for students to be succeed and go through all the difficulties they faced throughout those learning environments (Martin, Collie, & Nagy, 2021). The extent of students' learning losses is still unknown and will most likely have a long-term effect on students' profile and life (Andrew et al, 2020;McKendall et al, 2021;Tomasik et al, 2020).…”
Section: Covid-19 Pandemic Impact On School Studentsmentioning
confidence: 99%